Forming the early Chinese court : rituals, spaces, roles - Habberstad, Luke (Seattle : University of Washington Press, 2018)
Forming the Early Chinese Court builds on new directions in comparative studies of royal courts in the ancient world to present a pioneering study of early Chinese court culture. Rejecting divides between literary, political, and administrative texts, Luke Habberstad examines sources from the Qin, Western Han, and Xin periods (221 BCE-23 CE) for insights into court society and ritual, rank, the development of the bureaucracy, and the role of the emperor. These diverse sources show that a large, but not necessarily cohesive, body of courtiers drove the consolidation, distribution, and representation of power in court institutions. Forming the Early Chinese Court encourages us to see China's imperial unification as a surprisingly idiosyncratic process that allowed different actors to stake claims in a world of increasing population, wealth, and power.
Cover; Forming the Early Chinese Court; Title; Copyright; CONTENTS; Acknowledgments; Chronology of Dynasties and Han Reign Periods; INTRODUCTION: Forming the Early Chinese Court; PART 1 RITUALS; 1. Sumptuary Regulations and the Rhetoric of Equivalency; 2. Who Gets to Praise the Emperor?; PART 2 SPACES; 3. Parks, Palaces, and Prestige; PART 3 ROLES; 4. Politics, Rank, and Duty in Institutional Change; 5. The Literary Invention of Bureaucracy; CONCLUSION; Notes; Glossary; Bibliography; Index
Includes bibliographical references and index.
Description based on print version record.
JSTOR
Keywords: Courts and courtiers -- China -- History -- To 1500.; China -- Social life and customs -- 221 B.C.-960 A.D.; China -- History -- Qin dynasty, 221-207 B.C.; China -- History -- Han dynasty, 202 B.C.-220 A.D.; Chine -- Mœurs et coutumes -- 221 av. J.-C.-960.; Chine -- Histoire -- 221-207 av. J.-C. (Dynastie des Qin); Chine -- Histoire -- 202 av. J.-C.-220 (Dynastie des Han); HISTORY -- Asia -- China; Courts and courtiers; Han Dynasty (China); Manners and customs; Qin Dynasty (China); China; To 1500; History